Examining mindfulness and moral disengagement in doping: Perspective of Turkish wrestlers - Ayyildiz, Erdem; Kayabeşler, Hamza; Gülü, Mehmet; Yagin, Fatma Hilal; Aldhahi, Monira I.; García-Grimau, Elena; Al-Mhanna, Sameer Badri (Frontiers in Psychology, 2023)
Little is known about athletes' attitudes toward the use of prohibited substances in turkey. In particular, the World Anti-Doping Agency (WADA), initiating education policies for doping use and emphasizing doping-related education in studies conducted among Turkish wrestlers. Yet, it is unclear the extent to which the wrestlers comply and adhere to policies for doping use .Therefore, The overarching aimed of this study are two fold: firstly, to examine whether education and the status of being a national athlete (NA) alone have an effect on athlete mindfulness and depravity in doping. Secondly, the sub-dimensions of athlete mindfulness and immorality in doping were examined in terms of being a NA and having an education on doping. A total of 409 male wrestlers participated in this study. The results show that depravity in doping has a weak negative relationship with awareness and refocusing and a positive relationship with the judgment sub-dimension. The study provides insight into the athlete's conscious understanding of doping, the state of doping education, and the shift away from morality in doping.